(untitled) (Contemporary Mathematics, 2023)
Black pod disease is a major threat to cocoa production worldwide. A mathematical model for the spread of cacao black pod disease is presented in this article. The model takes into account several variables that influence the spread of the disease. A set of differential equations that are numerically solved using Runge-Kutta method embedded in MATLAB software are used to simulate the dynamics of disease transmission which form the basis of the model. Utilizing information from the literature and ecological observations from cocoa fields in West Africa, where black pod disease poses a serious threat to the production of cocoa, the model was verified. The model’s outcomes highlight the significance of early detection and rapid intervention in mitigating the severity of cocoa black pod disease outbreaks. Moreover, it emphasizes the importance of adopting integrated disease management approaches that consider fungicide administration and removal of infected pods. The usefulness of mathematical modeling as a tool for understanding and managing cocoa black pod disease is illustrated by this study.